Withaferin A inhibits lymphocyte proliferation, dendritic cell maturation in vitro and prolongs islet allograft survival - Kenjiro Kumano (Nature Portfolio, 2021)
Abstract The immunosuppressive regimen for clinical allogeneic islet transplantation uses beta cell–toxic compounds such as tacrolimus that cause islet graft loss. Previously we reported that the plant-derived steroidal lactone Withaferin A (WA) can protect islet grafts by inhibiting nuclear factor-kappa B (NF-κB). Since the NF-κB signaling pathway is essential for T-cell activation, we hypothesized that long-term WA administration may also provide an immunosuppressive effect. Treatment of BALB/c donor islets and C57BL/6N recipients with WA alone resulted in 80% islet graft long-term survival vs. 40% in low-dose FK506-treated mice. In vitro, WA significantly blocked mouse and human T-cell proliferation by CD3/CD28 bead stimulation and in mixed lymphocyte reaction assay. Treatment of immature dendritic cells with WA prevented their maturation in response to inflammatory stimuli, as seen by decreased expression of CD83 and human leukocyte antigen–DR isotype. Exosomes released by islets treated with WA contained significantly fewer proinflammatory molecules interleukin-6, interleukin-8, monocyte chemoattractant protein-1, interferon-gamma-induced protein-10, inducible nitric oxide synthase, and cyclooxygenase-2. In conclusion, WA treatment not only reduced inflammation but also prolonged allograft survival, possibly through suppression of dendritic cell maturation and T-cell proliferation. WA has the potential to inhibit both the innate and adaptive immune response to prolong allograft survival.